2018
DOI: 10.3201/eid2408.171030
|View full text |Cite
|
Sign up to set email alerts
|

Poverty and Community-Acquired Antimicrobial Resistance with Extended-Spectrum β-Lactamase–Producing Organisms, Hyderabad, India

Abstract: The decreasing effectiveness of antimicrobial agents is a global public health threat, yet risk factors for community-acquired antimicrobial resistance (CA-AMR) in low-income settings have not been clearly elucidated. Our aim was to identify risk factors for CA-AMR with extended-spectrum β-lactamase (ESBL)–producing organisms among urban-dwelling women in India. We collected microbiological and survey data in an observational study of primigravidae women in a public hospital in Hyderabad, India. We analyzed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 30 publications
0
28
1
1
Order By: Relevance
“…Likewise, in India where most studies included in the presented study had been performed, prevalence of ESBL‐P Enterobacteriaceae in a study performed in 2004 was 35.9% . In a recent study carried out in 2016 in India, this prevalence rose to 57.1% …”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…Likewise, in India where most studies included in the presented study had been performed, prevalence of ESBL‐P Enterobacteriaceae in a study performed in 2004 was 35.9% . In a recent study carried out in 2016 in India, this prevalence rose to 57.1% …”
Section: Discussionmentioning
confidence: 64%
“…38 In a recent study carried out in 2016 in India, this prevalence rose to 57.1%. 34 In a previous prospective study regarding antibiotic treatment of women with recurrent AB, the authors reported that women treated with antibiotic in fact had more recurrent episodes (4.4 times higher)…”
Section: Europementioning
confidence: 96%
See 2 more Smart Citations
“…La evidencia previa a este estudio permitió explicar correlaciones de determinantes con la RAM (18,19); sin embargo, no se ha dado suficiente importancia a la medición de desigualdades en la RAM de la N. gonorrhoeae. Colombia ofrece una oportunidad para investigarla aprovechando los desarrollos del Sistema de Información de la Protección Social (SISPRO).…”
Section: Palabras Claveunclassified